Synthesis, α-amylase inhibitory activity evaluation and in silico molecular docking study of some new phosphoramidates containing heterocyclic ring. (10th November 2020) - Altaff, SK. Md.; Raja Rajeswari, T.; Subramanyam, Ch.
Abstract: We have synthesized a series of phosphoramidates containing a heterocyclic moiety with good yields (88–95%) by the reaction of (E)-5-benzylidene-3-((2-hydroxyethoxy)methyl)thiazolidine-2, 4-dione with ethyl phosphorodichloridate followed by the reaction with various heterocyclic amines. The designed compounds were primarily screened for their ability to inhibit pancreatic α -amylase enzyme using in silico molecular docking approach. The compounds with good binding energies (−8.0 to −6.9 kcal/mol) when compared with standard drug, acarbose (−8.0 kcal/mol) were prompted for the synthesis. The structures of the newly prepared compounds were confirmed by their spectroscopic analyses. They were further screened in vitro for their inhibition toward α -amylase enzyme using acarbose as standard drug. All compounds exhibited moderate to good inhibition potential with IC50 values in the range of 54.14 ± 0.35 to 185.04 ± 0.53 µg/mL when compared with the standard drug (IC50, 50.47 ± 0.28 µg/mL). Especially, the compound (E)-2-((5-benzylidene-2, 4-dioxothiazolidin-3-yl)methoxy)ethyl ethyl 1, 3-dimethyl-2, 6-dioxo-1, 2, 3, 6-tetrahydropyrimidin-4-ylphosphoramidate (6f ) (IC50, 54.14 ± 0.35 µg/mL) and (E)-2-((5-benzylidene-2, 4-dioxothiazolidin-3-yl)methoxy)ethyl ethyl benzo[d]thiazol-2-ylphosphoramidate (6c ) (IC50, 57.02 ± 0.32 µg/mL) exhibited the best inhibition among the synthesized compounds. Graphical abstract: